Donor Management for Zakat Institutions: Experience From Indonesia - Ashadi Cahyadi; Sesilia Tri Andevi; Evina Nurmayani; Farizal Hammi Farij (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2025)
Purpose – This paper compares donor management in Indonesian zakat institutions. Then see how far the donation results are obtained. Design/methodology/approach – From the beginning, we followed qualitative rules with a case study approach in two national zakat institutions: the Inisiatif Zakat Indonesia (IZI) and the Lembaga Amil Zakat Nasional Dewan Dakwah (Laznas DD) Bengkulu Province Branch. Findings – Donor management determines the amount of donations received by zakat institutions. IZI emphasizes understanding donor characteristics through direct communication and social media. At the same time, Laznas DD focuses more on personal interaction through dawn activities and offers various donation methods. Laznas DD utilizes a Customer Relationship Management (CRM) system to maintain communication and increase donor satisfaction and loyalty. With various marketing strategies, both institutions have succeeded in expanding the reach of donors and optimizing zakat collection, increasing the effectiveness of fund management. Research implications – Our findings emphasize the importance of paying attention to the process and approach to donors. The ability to manage donors has a positive impact on the amount of zakat funds collected. Thus, practitioners need to adopt our findings or innovate to find appropriate strategies to maintain donors. Originality/value – Studies on philanthropic institution donors have been repeatedly reviewed. Unfortunately, donor management in the context of zakat institutions is forgotten. Our study fills this gap by comparing two zakat institutions in Indonesia. Keywords - Donor management, Zakat Institutions, Fundraising, Indonesia. Paper type - Research paper